2021
DOI: 10.21203/rs.3.rs-1070116/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative And Phylogenetic Analyses of Six Kenya Polystachya (Orchidaceae) Species Based On The Complete Chloroplast Genome Sequences

Abstract: Background: Polystachya Hook. is a large pantropical orchid genus (c. 240 species) distributed in Africa, southern Asia and the Americas, with the centre of diversity in Africa. Chloroplast (cp) genomes of plants are highly conserved and can provide much more informative DNA sites and generate much better resolution for plant phylogenies. However, for Polystachya, the whole cp genome including its structure features are yet unknown and its phylogenetic placement of the genus within the Orchidaceae is still unc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 106 publications
(152 reference statements)
0
3
0
Order By: Relevance
“…Among seven species of the genus Polystachya, there were a variation of 2 (P. dendrolli ora) and 8 (P. modesta) dispersed repeats. The authors indicated that variations in these repetitions may indicate exibility in the evolutionary process 39 and that this may be considered an indicator of diversity among species, important for the phylogeny of the genus 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Among seven species of the genus Polystachya, there were a variation of 2 (P. dendrolli ora) and 8 (P. modesta) dispersed repeats. The authors indicated that variations in these repetitions may indicate exibility in the evolutionary process 39 and that this may be considered an indicator of diversity among species, important for the phylogeny of the genus 38 .…”
Section: Discussionmentioning
confidence: 99%
“…loss and pseudogenization (Wicke and Naumann, 2018), which are also prevalent in autotrophic plants, including conifers (Wakasugi et al, 1994;Ni et al, 2017), Orchidaceae (Jiang et al, 2022), and Papavaraceae (Xu and Wang, 2021), suggesting that this is a random phenomenon in the evolution of photosynthetic lineages.…”
Section: Pseudogenization and Sequence Inversionmentioning
confidence: 99%
“…Plastid genomes (plastomes) are highly conserved, comprising linear, branched or occasionally circular molecules that usually contain a large, inverted repeat (IR) and large and small single-copy regions (LSC and SSC). Due to their conserved structure and low rate of nucleotide substitution, plastome data has made substantial contributions to phylogenetic studies for many plant groups (Jansen & Ruhlman, 2012; Jiang et al, 2022; Liu et al, 2022; Xia et al, 2022; Xu et al, 2022; Yu et al, 2022). Despite the high level of plastome structural conservation in seed plants, rearrangements, including inversions, expansion and contraction of the IR, and IR loss occurred in unrelated lineages of gymnosperms and angiosperms (Ruhlman & Jansen, 2021).…”
Section: Introductionmentioning
confidence: 99%